Efeitos da adição de biossólido no crescimento inicial de Eucalyptus citriodora Hook - Pérez, Paula Vergili (2008)
Nowadays the concerns about the high amount of organic material produced by human activities refer to its reutilization. Thus, the usage of treated sewer mud as an organic fertilizer and physical conditioner of soils has been researched for several cultures, especially forest species. Hence this work aimed to evaluate the effects of the addition of biosolids doses in the initial development of the Eucalyptus citriodora Hook. For this experiment it was utilized doses of biosolids equivalents at 0, 10, 20, 30 and 40 t ha-1. With their incorporation to a superficial layer of 20 cm. The parameters evaluated were: plants length; number of leaves, foliar area, colon diameter and aerial and radicular dry biomasses on 60, 120, 180, 240 and 300 days after the transplant. The analysis of the results pointed that the viability of the use is between the doses 30 e 40 t ha -1, because their effects are positively demonstrated in the parameters: plant length (increases average between 30 e 40 t ha-1 equal to 38,85 cm) and number of leaves (increases average between 30 e 40 t ha-1 of 43,9 leaves, higher than other treatments that got an average equal to 35,62 leaves), as well as in the colon diameter and aerial and dry biomass. Evidences on the reduction of the radicular dry biomass accumulation with the application of increasing doses of biosolid, the dose 10 t ha-1 stood out, because this got the average higher (99,12g) than the other treatments (31,48), indicating a priority in the growing strategy of the fast development specie, which commercial interest is emphasized by the production of wood and leaves, implies a recommendation of doses of 30 t ha-1 that is able to reduce expenses in transport and in application comparatively to a doses of 40 t ha -1